LEGAL PROTECTION FOR WORKERS THAT HAVE BEEN TERMINATED DURING THE COVID-19 PANDEMIC - Agoes Djatmiko; Elisabeth Pudyastiwi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study aims to determine legal protection for workers who experience layoffs during the covid-19 pandemic. In this study, the type of research used is normative legal research using legal material collection techniques in the form of document studies or literature studies. The approach used in this research is a statutory approach and the sources of legal materials used are primary legal materials, secondary materials, and tertiary legal materials. The results of the study indicate that Termination of Employment has a negative impact on workers because they lose their jobs so that it also has an impact on increasing the poverty level of the Indonesian people. Due to the emergence of PSBB regulations from the government, of course, the space for work is getting narrower and layoffs are increasingly happening, therefore the regulation of Law no. 13 of 2003 concerning Manpower and also the role of the government is very important to overcome the occurrence of layoffs that are not in accordance with the laws and regulations.